Review of the Neoaliturus fenestratus (Herrich-Schäffer, 1834) species group (Homoptera: Auchenorrhyncha: Cicadellidae: Deltocephalinae: Opsiini) from Russia, Kazakhstan, and Central Asia - Tishechkin, Dmitri Yu. (Zootaxa, 2021)
In Russia, Kazakhstan, and Central Asia the Neoaliturus fenestratus species group includes eight species. Illustrated descriptions, oscillograms of male calling signals, and data on host plants and distribution for all species are given. One new species from European Russia and two new species from Kazakhstan and Central Asia are described, and the synonymy N. fenestratus (Herrich-Schäffer, 1834) = N. lituratus Dubovskiy, 1966, syn. n. is established. Considerations concerning possible modes of diversification of species of this group are provided.